Effect of feedback-integrated reflection, on deep learning of undergraduate medical students in a clinical setting - Zainab Maqsood; Madiha Sajjad; Raheela Yasmin (BMC Medical Education)
Abstract Background Reflection fosters self-regulated learning by enabling learners to critically evaluate their performance, identify gaps, and make plans to improve. Feedback, in turn, provides external insights that complement reflection, helping learners recognize their strengths and weaknesses, adjust their learning strategies, and enhance clinical reasoning and decision-making skills. However, reflection alone may not produce the desirable effects unless coupled with feedback. This study aimed to investigate the impact of feedback integrated reflection on meaningful learning and higher order MCQ score among under-grade medical students. Objective To evaluate the impact of feedback-integrated reflection versus reflection alone on higher-order MCQ scores among undergraduate medical students in a gynecology clinical setting. Methods A randomized controlled trial was conducted with 68 final-year medical students randomly assigned to a study group (feedback-integrated reflection) and a control group (reflection alone). Both groups completed a pre-test, followed by six daily teaching sessions on gynecology topics. Participants engaged in written reflections after each session, and the study group additionally received individualized feedback. Independent sample t-tests were used to compare pre and post-test scores between the groups, while paired t-tests assessed within-group improvements. Results Pre-test scores were comparable between the study group (11.68 ± 2.60, 38.93%) and the control group (11.29 ± 2.38, 37.15%; P = 0.52). Post-test scores showed a significant improvement in the study group (20.88 ± 2.98, 69.32%) compared to the control group (15.29 ± 2.66, 51.00%; P = 0.0001). The percentage gain in learning was 35.43% for the control group (reflection alone) and 78.77% for the study group (feedback-integrated reflection). The normalized learning gain (NLG) was calculated to compare the effectiveness of the intervention (feedback-integrated reflection) with that of the control (reflection alone). The study group demonstrated a mean normalized learning gain of 69.07%, compared to 29.18% in the control group. The net learning gain, calculated as the difference in normalized learning gains between the study and control groups, was found to be 39.89%. Conclusion The findings highlight the effectiveness of feedback-integrated reflection versus reflection alone in fostering deeper learning by improving higher-order MCQ scores in a gynecologic setting in the undergraduate medical education. Trial registration This trial was registered retrospectively on 27th July 2024. Trial registration no is CTU/07/2024/010/RMU.